Kartogenin Induces Chondrogenesis in Cartilage Progenitor Cells and Attenuates Cell Hypertrophy in Marrow-Derived Stromal Cells - Yang, Daniel S.; Trivedi, Jay; Betensky, Daniel; Desai, Salomi; Owens, Brett D.; Jayasuriya, Chathuraka T. (Current Stem Cell Research & Therapy, 2025)
IntroductionKartogenin (KGN) is a synthetic small molecule that stimulates chondrogenic cellular differentiation by activating smad-4/5 pathways. KGN has been proposed as a feasible alternative to expensive biologic growth factors, such as transforming growth factor β, which remain under strict regulatory scrutiny when it comes to their use in patients. This study reports the previously unexplored effects of KGN stimulation on cartilage-derived mesenchymal progenitor cells (CPCs), which have been shown to be effective in applications of cell-based musculoskeletal tissue regeneration.MethodsGene expression via RT-qPCR analysis was used to determine the effects of KGN treatment on CPCs and human marrow derived stromal cells (BM-MSCs). The expression of SOX9, COL1, COL2, COL10, RUNX2, and MMP-13 were quantified following 3-10 days of KGN treatment. Additionally, soluble MMP-13 protein was quantified using ELISA. A GAG assay was used to compare proteoglycan production. Cell viability was measured in response to different doses of KGN using an MTT assay.ResultsOur findings demonstrate that KGN treatment significantly increased markers of chondrogenesis, SOX9 and COL2 following 3-10 days of treatment in human CPCs. KGN treatment also resulted in a significant dose-dependent increase in GAG production in CPCs. The same efficacy was not observed in human BM-MSCs; however, KGN significantly reduced mRNA expression of cell hypertrophy markers, COL10 and MMP-13, in BM-MSCs. Parallel to these mRNA expression results, KGN led to a significant decrease in protein levels of MMP-13 both at 0-5 days and 5-10 days following KGN treatment.ConclusionIn conclusion, this study demonstrates that KGN can boost the chondrogenicity of CPCs and inhibit hypertrophic terminal differentiation of BM-MSCs.
Keywords: meniscus